Die–offs, reproductive failure, and changing at–sea abundance of murres in the Bering and Chukchi Seas in 2018. (December 2020) - Romano, Marc D.; Renner, Heather M.; Kuletz, Kathy J.; Parrish, Julia K.; Jones, Timothy; Burgess, Hillary K.; Cushing, Daniel A.; Causey, Douglas
Abstract: Common and thick–billed murres are among the most numerous and widespread seabirds in the northern hemisphere though they appear to be especially susceptible to mass die–off events. During the spring and summer of 2018, the Bering Sea experienced warmer than average sea temperatures following a winter of unprecedented, near complete lack of sea ice. To determine if breeding murres were negatively affected by these warm sea temperatures, surveys at most of the major murre breeding colonies in the eastern Bering and eastern Chukchi seas were conducted during the 2018 breeding season. Nearly all colonies surveyed experienced near-complete reproductive failure. Concurrently, above average levels of murre mortality were observed, primarily at St. Lawrence Island and in the Bering Strait region. The timing of this mortality is somewhat unusual and concerning as it occurred during the breeding season. Based on surveys at sea, overall murre abundance offshore was generally lower in 2018 compared to recent years (2012–2017), particularly in the northern Bering Sea, yet mean density for thick–billed murres increased in the Chukchi Sea. Reproductive failure is rare at monitored murre colonies within the study area and the widespread reproductive failures observed in 2018 were unprecedented over four decades of monitoring, but consistent with the reproductive failure of murres documented in the Gulf of Alaska and southeastern Bering Sea following a large murre die–off in 2015–2016. The combination of large–scale reproductive failure, evidence of elevated levels of mortality, and low abundance of birds offshore suggest that murres experienced severe distress in the Bering and Chukchi sea region during the summer of 2018.